Who'd be a nurse?: Some evidence on career choice in Australia - Dockery, Alfred Michael; Barns, Angela (National Institute of Labour Studies, 2005)
In the context of on-going shortages of nurses this paper looks at factors shaping the decision to enter nursing as a career. Evidence from three different Australian sources is drawn upon: a national panel survey of young school leavers, a survey of first year university students in WA and in-depth interviews with 28 young women studying for their WA Tertiary Entrance Examinations. The results concur with previous studies that have found entrants to nursing courses to be of average-to-be low academic ability and socio-economic status, to have an affinity for caring and to place greater relative emphasis on balancing family and work rather than on career success. Some new insights into the factors influencing the decision to become a nurse further highlight the importance of perceptions of gender roles in society and are consistent with psychological and feminist approaches to career choice.